The effectiveness of the human resources management strategy in improving employee performance by applying it to Meera Company in Asir Region - Al-Qahtani, Maha Mushabab Ali; Fara, Ebtisam Mohammed Khalid; Al-Qahtani, Wejdan Mana Saeed; Badr, Abdullah Mahmoud Mohamed (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to measure the effectiveness of the strategy of human resources management in improving the performance of employees by applying it to the Mira company in the Asir region. Researchers used The study used the descriptive analytical method and the questionnaire as a tool for collecting study data, and due to the limited study population, which is (75) individuals, the comprehensive survey method was used, where The number of responses received was (74), and to analyze the study data, the SPSS-25 statistical package and the AMOS-23 statistical package for structural modeling were employed. The study reached a number of results, the most important of which were: The human resource management strategy explains approximately (0.67) of the total discrepancy in the work performed as a result of the change in the company’s human resource management strategy, and the human resource management strategy explains approximately (0.76) of the total discrepancy in commitment As a result of the change in the company’s human resource management strategy, the human resource management strategy (0.69) also explains approximately the total variance in the quality of work as a result of the change in the company’s human resource management strategy. The results also showed that the human resource management strategy explains (0.65) of the total variance in improving the delivery time as a result of the change in the company’s human resource management strategy, and the human resource management strategy explains approximately (0.70) of the total variance in flexibility and output as a result of the change in the strategy of human resource management. The company’s human resources, and the human resource management strategy explains approximately (0.77) of the total variance in cost as a result of the change in the company’s human resource management strategy.
Keywords: strategy; management; human resources; employee performance; Meera Company